Physical-hydric properties of Oxisol and Quartzipsamment associated with the application of wood ash - Thiago F. Duarte; Edna M. Bonfim-Silva; Tonny J. A. da Silva; Márcio Koetz; Gabrielly F. Lima (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The addition of wood ash to soil is an alternative to disposing of this residue. However, the effects of wood ash on soil physical-hydric properties remain divergent. In this study, the effects of added wood ash on the soil water characteristic curve, gravitational water, field capacity, total available water, and saturated hydraulic conductivity were evaluated in Oxisol (40% clay and clay texture) and Quartzipsamment (6% clay and sand texture). The experimental design was completely randomized in a 2 × 4 factorial scheme, where the factors were two soils and four doses of wood ash, with three replicates. The wood ash came from an agribusiness and was the result of burning eucalyptus wood. The wood ash doses were 0, 16, 32, and 64 g dm-3. The gravitational water, field capacity, and total available water were fitted to a quadratic model as a function of the wood ash dose. The saturated hydraulic conductivity decreased linearly with an increase in wood ash dose for both soil classes. The soil water characteristic curve only increased significantly (p ≤ 0.05) with a wood ash dose of 64 g dm-3. The increase in total available water was more evident in Oxisol than that in Quartzipsamment, with increments of 64 and 31%, respectively, at a maximum dose of 64 g dm-3 of wood ash.